THE EFFECTIVENESS OF STUDENT TEAM ACHIEVEMENT DIVISION AS A STRATEGY TO HELP STUDENTS COMPREHEND ANALYTICAL EXPOSITION TEXT (RETAIN, 2015)
Abstract Reading activity is not simply defined as an activity in which readers read word per word in the text. It means that the students are expected not only to read the whole text but also to comprehend the meaning of the text and to understand what happens in the text. To have better comprehension of a text, readers are expected to have a strategy and discuss what they read with other people in a group. Therefore, strategy is one of the factors which makes the teaching reading efficient. Thus teachers need to provide an alternative strategy to help students comprehend the text. Owing to this situation, teachers may use cooperative learning (Students Team Achievement Divisions) in conducting the teaching learning process. The goal of this research is to find out whether there is a significant improvement of the students’ reading comprehension in analytical exposition text after being taught by using STAD strategy. The design used was experimental quantitative which applies pre and post-design. The researcher chose cluster random sampling as his sampling. The instrument used in this research was multiple choice test and the Sample t-test was used as the data analysis technique. The result showed that there was a significant improvement of the students’ reading comprehension in analytical exposition text after being taught by using STAD strategy. It could be seen from the p value which was less than .05. Thus, it indicated that there was an improvement. So it can be concluded that there was a significant difference between the students’ reading ability before and after being taught using STAD technique. It means that STAD technique can improve students’ reading achievement. Furthermore, the researcher suggests that Since STAD strategy in teaching reading comprehension is applied at the second grade of Senior High School, other researchers can conduct this technique on different level of students (like Junior High School) or on different skills like speaking. Keywords: Student Team Achievement Division, Reading, Analytical Exposition Text. Abstrak Kegiatan membaca dapat diartikan sebuah aktifitas dimana para pembaca membaca kata demi kata didalam teks. Untuk mendapatkan pemahaman sebuah teks yang lebih baik, para pembaca diharapkan mempunyai strategi. Oleh karena itu, strategi merupakan salah satu faktor yang dapat membuat pembelejaran membaca menjadi efisien dan para guru harus menyiapkan sebuah alternatif strategi untuk membantu para siswanya memahami teks.. Mengacu pada hal tersebut, para guru dapat menggunaka pembelajaran yang kooperatif (Divisi pencapaian siswa dalam tim) dalam proses pengajaran. Tujuan dari penelitian ini adalah untuk mencari tahu apakah terdapat perunahan signifikan pemahaman membaca para siswa dalam teks eksposisi analisis setelah pemberian pembelajaran dengan mengunaka strategi divisi pencapaian siswa dalam tim. Desain penelitian yang digunakan dalam studi ini adalah eksperimental kuantitatif yang mengaplikasikan pre and post-design. Peneliti mengunakan cluster random sampling sebagai desain sampelnya. Instrument penelitian yang dipakai dalm studi ini merupakan test pilihan ganda dan Sample t-test digunakan sebagai teknik analisis data. Hasil menunjukkan bahwa terdapat perunahan signifikan pemahaman membaca para siswa dalam teks eksposisi analisis setelah pemberian pembelajaran dengan mengunaka strategi divisi pencapaian siswa dalam tim. Hal ini dapat dilihat dari nilai p yang kurang dari .05. Oleh karenanya, hal ini mengindikasikan bahwa terdapat peningkatan. Dapat disimpulkan bahwa terdapat perubahan signifikan antara pemahaman membaca para murid sebelum dan setelah pembelajarn dengan menggunakan strategi divisi pencapaian siswa dalam tim. Hal ini berarti strategi STAD dapat meningkatkan pemahaman membaca para siswa. Terlebih, karena strategi ini diaplikasikan dalam pembelajaran membaca SMA kelas dua, maka dari itu peneliti menyarankan para peneliti lainnya untuk mengaplikasikan strategi ini dalam tingkatan murid yang berbeda (Seperti murid-murid sekolah menengah pertama) atau dalam keahlian yang berbeda seperti berbica. Kata Kunci: Student Team Achievement Division, Membaca, teks analisis eksposisi.